C2 Subcutaneous Stimulation for Failed Back Surgery Syndrome: A Case Report. Issue 6 (5th June 2013) - De Ridder, Dirk; Plazier, Mark; Menovsky, Tomas; Kamerling, Niels; Vanneste, Sven
<x xml:space="preserve">Abstract</x> Objective Failed back surgery syndrome (FBSS) is a term embracing a constellation of conditions that describes persistent or recurring low back pain, with or without sciatica following one or more spine surgeries. It has been shown in animals that electrical stimulation of the high cervical C2 area can suppress pain stimuli derived from the L5‐S1 dermatome. It is unknown whether C2 electrical stimulation in humans can be used to treat pain derived from the L5‐S1 area, and a case is reported in which subcutaneous C2 is applied to treat FBSS. Case A patient presents to the neuromodulation clinic because of FBSS (after three lumbar diskectomies) and noninvasive neuromodulation is performed consisting of transcutaneous electrical nerve stimulation (TENS) at C2. The C2 TENS stimulation is successful in improving pain. It induces paresthesias in the C2 dermatome above a certain amplitude threshold, but does not generate paresthesias in the pain area. However, the patient becomes allergic to the skin‐applied TENS electrodes and therefore a new treatment strategy is discussed with the patient. A subcutaneous C2 electrode is inserted under local anesthesia, and attached to an external pulse generator. Methods Three stimulation designs are tested: a classical tonic stimulation, consisting of 40 Hz stimulation, a placebo, and a burst stimulation, consisting of 40 Hz burst mode, with five spikes delivered at 500 Hz at 1000 μsec pulse width and 1000 μsec interspike interval. Results The patient's stimulation results demonstrate that burst mode is superior to placebo and tonic mode, and she receives a fully implanted C2 electrode connected to an internal pulse generator via an extension wire. Conclusion The burst design is capable of both suppressing the least and worst pain effectively, and she has remained almost pain‐free for over three years.